The Raising of the 'One Piece' Flag during Independence Day: A Public Order Law and Human Rights Perspective - M. Reza Saputra; Nabila Hilyatunisa (Yayasan Cerdas Pedia Indonesia, 2025)
This article examines the legal and constitutional implications of raising the “One Piece” flag during Indonesia’s 80th Independence Day celebrations from a public order law and human rights perspective. The controversy arose when government authorities threatened criminal sanctions under Article 24(1) of Law No. 24/2009 on the National Flag, Language, Emblem, and Anthem, alleging that the display of a fictional pirate emblem alongside the national flag constituted desecration. The study identifies tensions between state interests in preserving national symbols and citizens’ rights to freedom of expression under Articles 28E(3) and 28F of the 1945 Constitution, constrained by limitation clauses in Article 28J(2). Employing doctrinal and comparative methods, the research analyzes statutory provisions, Constitutional Court precedents, and international benchmarks from the United States and Germany to evaluate the proportionality and necessity of criminal enforcement measures. Findings reveal that Law No. 24/2009’s text focuses on protecting the national flag itself and does not explicitly proscribe the peaceful display of alternative symbols that respect the flag’s dignity. The government’s prosecutorial threat thus appears inconsistent with the principles of nullum crimen sine lege and disproportionate under international human rights norms, including Article 19(3) of the ICCPR. The article concludes that non‐criminal alternatives such as public education campaigns and legislative clarification incorporating mandatory proportionality tests would better reconcile national unity objectives with constitutional liberties. These recommendations aim to guide future legislative reform and judicial interpretation, ensuring that symbolic political expression remains protected within Indonesia’s democratic framework.